Avaliação da ocorrência de constrição mecânica do arco na soldagem A-TIG de aços inoxidáveis austeníticos - Guilherme Simoes Pandolfi (2016)
This paper aims to evaluate, by filming the electrical arc and evaluating its electrical parameters, indications of its constriction by the thermal and electrical insulation caused by oxides of a single component in A-TIG and FB-TIG welding of austenitic stainless steels. Changes in arc dimensions, in its electric voltage and in weld bead morphology by three single component oxide fluxes (SiO2, Cr2O3 e Al2O3) applied with two surface densities (30 e 60 g/m2), and with and without a flux free central strip (of 1, 2, and 4 mm) were studied. Results showed no significant change in width of the electric arc for the experimental conditions used, therefore, not supporting a possible mechanical constriction in the electric arc by oxide electrical and thermal insulation. Lateral filming indicated that the arc is delayed by the fluxes with silica causing the strongest effect. The presence of clean central strip in the flux layer decreased weld penetration and weld bead cross section, besides the reduction of the width of the bead. Results also suggest that a minimum bead width exists for an opening of about 2 mm. Arc constriction is usually used to explain bead width reduction by a flux-free the central opening. However, this can also be relate to Marangoni convection. Therefore, the results of the present work seem to support Marangoni convection as the main mechanism responsible for increasing penetration in A-TIG welding of stainless austenitic steels.